The effectiveness of cognitive-behavioural therapy on depression in the elderly - Kitsumban,V. (Joanna Briggs Institute, 2015)
Review Question/ Objective The aim of this review is to examine the best available evidence to determine the effectiveness of Cognitive-Behavioural Therapy on treating depression in the elderly. The specific review question is: What is the effectiveness of Cognitive-Behavioural Therapy on treating depression in elderly people? Inclusion Criteria Types of participants This review will consider all studies examining the treatment of older persons aged 60 years or more who had a score of 10 to 29 (mild to moderate level of depression) on the Beck Depression Inventory and were residents in a nursing home setting or in the community. Types of intervention The intervention of interest to this review is Cognitive-Behavioural Therapy, which is based on cognitive theory and designed to consciously identify automatic negative thoughts and their associated problems, and to develop alternative thinking patterns and problem solving, aimed at reducing the level of depression. Types of outcome measures The primary outcome of interest is a change in depressive symptoms. Thus, this will be defined by the relative change in scores from pre-test to post-test as measured on a standard psychological test. The severity of depression is measured by validated scales, for example, Beck Depression Inventory (BDI-IA)2. The test contains 21 items, most of which assess depressive symptoms on a Likert scale of 0-3. People are asked to report on their mood and feelings over the past week, including the day of the test.